Pengaruh Model Pembelajaran Discovery learning Berbantuan Google Sites pada Pembelajaran IPAS Terhadap Literasi Sains Siswa Sekolah Dasar - I Gede Rika Suardita; I Ketut Suparya; I Putu Suardipa; I Ketut Ngurah Ardiawan (IJPSE Indonesian Journal of Primary Science Education, 2025)
This study examines the low level of science literacy among students, which is due to teacher-centered science education dominated by lecture methods, a lack of student motivation and engagement, and a lack of student focus during learning. This study examines the effect of the Discovery learning model, assisted by Google Sites, on science education and its impact on the science literacy of fifth-grade students. The study employed a quasi-experimental design with a pretest-posttest control group. The study population consisted of 232 fifth-grade students from SDN Gugus 1 in Buleleng District. Through a lottery, the sample was randomly selected, with SDN 2 Anturan selected as the experimental group of 34 students and SDN 3 Kalibukbuk selected as the control group of 33 students. Data were collected through essay tests. Additionally, data was collected through documentation. The tests were then validated for validity, reliability, and difficulty level. Descriptive and inferential statistics (t-test) were used for data analysis. The results of the analysis showed that the calculated t-value was greater than the critical t-value (34.522 > 1.669), indicating a significant difference in science literacy between the two groups. Therefore, there was a significant difference in science literacy among IPAS students who were taught using the discovery learning model with Google Sites compared to those who were not.